1907 Iowa Acts 81 - (:unkn) unknown (My University, 1907)
Ch. 76, § V(e) : Prohibited keeping benzine, benzole, dynamite, ether, fireworks, gasoline, Greek fire, gunpowder in excess of twenty-five pounds, other explosive, phosphorous, calcium carbide, petroleum, or any of its products of greater inflammability.
Keywords: GUNPOWDER - STORAGE